A triple-resonance Raman chip for simultaneous enhancement of Stokes and anti-Stokes lines utilizing both localized and non-localized plasmonic resonance. (21st August 2015) - Lin, Jiao; Zhang, Yuan; Lee, El-Hang; He, Sailing
Abstract: In this paper we report a triple-resonance surface-enhanced Raman scattering (SERS) chip that is able to provide simultaneous field enhancement for both the Stokes and anti-Stokes lines. The structure consists of an array of periodic gold bowties placed on the surface of a uniform gold film. It can support two localized surface plasmonic resonances (LSPRs): an electric dipole binding resonance (EDBR) and a magnetic dipole resonance (MDR). A third field enhancement peak is obtained by utilizing the strong interaction between the non-localized surface plasmonic resonance (non-localized SPR) and the LSPR, which greatly raises the field enhancement for the non-localized SPR. In addition, a gold strip-line resonator is incorporated to further enhance the local field intensity. Consequently, the field enhancement of the three peaks are all increased. Compared with the same structure without strip, the periodic bowtie-strip compound structure on gold film can gain as much as ∼22.8 times and ∼3.6 times larger Raman intensity enhancement simultaneously for both the Stokes and anti-Stokes lines.